Efektivitas Infrared Pada Penderita Frozen Shoulder : Literature Review - Bayu Febrianto; Nyimas Najwa Putri Rahayu Khairunnisa; Dini Nur Alpiah (Termometer: Jurnal Ilmiah Ilmu Kesehatan dan Kedokteran, 2024)
Frozen shoulder is clinically described as persistent shoulder pain and advanced exacerbation of the shoulder joint leading to upper extremity activity, significant disability, and functional limitations. The intervention that can be given to frozen shoulder is the administration of infrared which aims to stimulate heat and nociceptive receptors to feel warmth thereby increasing blood flow to the muscles and improving muscle stiffness and pain. The aim of this research is to determine the effectiveness of the infared modality to reduce pain in frozen shoulder patients. The research method used is a literature review approach, by searching for references using the PICO method. Results: From the 4 journals studied, infrared had an effect on reducing pain in patients suffering from frozen shoulder, with a therapy duration of 15-30 minutes and a p-value of p<0.05 showing a significant effect. Conclusion: infrared has the effect of reducing pain in patients with frozen shoulder. From the journals quoted, it is proven that there is a degree of reduction in pain when measured using the Visual Analogue Scale (VAS).